Cycle Duration in Production with Periodicity – Evidence from Turkey - Yýlmaz Akdi; Serdar Varlik; Hakan Berument (International Econometric Review (IER), 2018)
In this paper, the sub-cycles in two economic activity measures are analyzed by using periodogram analyses. Our results from Turkish data suggest that industrial production and capacity utilization rate consist of various cycles including seasonal cycles. These series also have common cycles which correspond about four and seven years. Last, industrial production has also additional cycles compare to capacity utilization ratio cycle.
Keywords: C22; C32; E32; 330; Business Cycle; Spectral Analysis; Periodogram